Fundamental Principles of the Ideal Islamic Community (Khair Ummah) in Preserving Religious Solidarity in the Islamic World - Barazili, Sigit; Syukur, Abdul (STAI Miftahul Ula Nganjuk, 2023)
This study delves into the concept of the ideal Islamic society, often known as